How have the Care Act 2014 ambitions to support carers translated into local practice? Findings from a process evaluation study of local stakeholders' perceptions of Care Act implementation. (11th October 2021) - Marczak, Joanna; Fernandez, Jose‐Luis; Manthorpe, Jill; Brimblecombe, Nicola; Moriarty, Jo; Knapp, Martin; Snell, Tom
Abstract: The Care Act 2014 imposed new statutory duties on English local authorities in relation to family or informal carers and it broadened carers' statutory entitlements to assessment, care and support, irrespective of eligibility for local authority funding of the person they care for. Despite this legislative framework, local authorities appear to be translating the new legal obligation into practice in different ways. This paper draws on evidence from in‐depth interviews held during 2017–2018 with key stakeholders in three English local authorities to investigate whether and how local efforts meet the Act's intention of supporting carers. We explored local goals associated with supporting carers, local authorities' approaches to needs assessment and service provision as well as barriers and facilitators to adoption of the new legal obligations towards carers. The paper draws on Twigg, J., & Atkin, K. (1995), typology to explore perceptions of local stakeholders of the interaction between formal care system and carers post‐Care Act. The findings indicate that despite a clear Care Act emphasis on meeting carers' needs, when faced with financial constraints the formal care system approaches carers mainly as a resource and often supports carers to keep cared‐for people away from health and social care systems. Although replacement care is a vital element in the Care Act's ambitions to support carers, in sampled authorities, it was often newly being subject to needs thresholds and financial assessment of people they care for, leading to reported conflicts of interests between carers' needs and those of cared‐for‐people. The Care Act is nonetheless seen as having made progress in legitimising carers' needs as clients. Social care professionals increasingly emphasise the importance of meeting carers' needs and well‐being as valued and desirable outcomes.